Application of Computer Assisted Instruction Model in Physics Learning - Harvei Desmon Hutahaean; Muhammad Isnaini; Juniar Hutahaean (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid advancement of technology has significantly transformed various sectors, including education, leading to the emergence of e-learning. This approach utilizes electronic media to facilitate faster and more efficient absorption of learning materials by students. One form of e-learning is the Computer Assisted Instruction (CAI) model, which integrates information technology components such as communication tools, audio, video, and images into a cohesive multimedia platform. The implementation of CAI in e-learning enables flexible learning delivery by allowing educators to present instructional content and engage learners interactively, whether in one-on-one sessions or in small groups. This model enhances the learning experience by incorporating tutorials and multimedia presentations. Physics, as a branch of natural science, plays a critical role in shaping human reasoning and intellectual development. It investigates the fundamental elements of the universe, the forces acting upon them, and the resulting interactions, ranging from subatomic particles to cosmic phenomena. Natural Science itself is more than just the accumulation of knowledge in the form of facts or theories—it also involves systematic inquiry and discovery processes. Applying the CAI model in high school physics education, particularly in the topic of straight-motion kinematics, is expected to improve students’ comprehension and conceptual understanding. Based on evaluations from media and subject matter experts, as well as product testing, the instructional media developed has been rated highly feasible, receiving an 86% approval score from users.